2021
DOI: 10.3389/fneur.2021.627183
|View full text |Cite
|
Sign up to set email alerts
|

Key Characteristics of Nitrous Oxide-Induced Neurological Disorders and Differences Between Populations

Abstract: Background: Nitrous oxide (N2O), commonly known as laughing gas, is inhaled recreationally because it produces the feelings of euphoria and freedom from pain. The risk of neurological dysfunction secondary to N2O abuse and its clinical diagnosis are, however, not yet sufficiently recognized, especially in China. Here, we have summarized the key clinical characteristics of N2O-induced neurological disorders.Materials and Methods: We recruited 20 patients with N2O-induced neurological disorders and analyzed thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…For example, Yu et al reported 54% loss to follow-up in their cohort study of 110 patients [23]. On average the prognosis is found to be good with percentages of recovery varying between 67% and 95% [12,23,24]. In our study, a large proportion of patients (81%) improved completely or with mild residual symptoms.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…For example, Yu et al reported 54% loss to follow-up in their cohort study of 110 patients [23]. On average the prognosis is found to be good with percentages of recovery varying between 67% and 95% [12,23,24]. In our study, a large proportion of patients (81%) improved completely or with mild residual symptoms.…”
Section: Discussionsupporting
confidence: 54%
“…It is uncertain whether the reported amount and duration of N 2 O use is correct and therefore no correlation could be made with the severity of symptoms and EDx changes. Unfortunately, it is well known that in the N 2 O‐abuse population there is a large proportion lost to follow‐up, also seen in our cohort (40%) [14, 23, 24]. Therefore, data about ongoing N 2 O abuse were insufficient.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Due to a lack of supervision measures and a large population, the number of cases of N 2 O-related neurological disorders in China has increased rapidly since 2016 (6)(7)(8)(9)(10)(11)(12). Published studies have typically focused on symptom presentations, imaging characteristics, laboratory findings, and distinctions from other subacute combined degenerations (SCDs).…”
Section: Introductionmentioning
confidence: 99%